Estilos de crianza parental y su relación con las conductas disruptivas en niños. - Chugñay Ilbay, Alexandra Marili (2023)
ABSTRACT: Several studies identify the importance of exercising in favor of parental style, since the social, emotional and affective development of the child and the formation of positive and negative behaviors depend on it. The purpose of the following research was to characterize parental styles and their relationship to disruptive behaviors among Latin American children. Methodologically, the study was set by literature review, quantitative approach, descriptive level and cross-sectional design, in which a population of 3,229 scientific papers from Latin America were consulted, which after going through a filtering process and methodological quality review by means of the CRF-QS instrument, formed a sample of 45 scientific papers. In the results obtained, it was concluded that the authoritarian style is related to rebelliousness, indiscipline, disregard of orders and attention problems; the permissive style to aggressiveness and disobedience and the negligent style to antisocial behaviors. Moreover, it has been established that the authoritarian style is the one most used by parents because of a trans-generational model. Finally, the effects of parental styles are linked to other factors such as culture, family type and socio-economic status.